Analysis of Non-Immune Hyrops Fetalis: Evaluation of 15 Cases - Aran, Turhan; Osmanağaoğlu, Mehmet; Bozkaya, Hasan (Gynecology Obstetrics & Reproductive Medicine, 2012)
OBJECTIVES: To evaluation the ultrasound characteristics, etiological factors and perinatal outcome in hydrops fetalis. STUDY DESIGN: A total of 15 hydrops fetalis presented in our perinatology unit, were studied prospectively. RESULTS: The etiology of non-immune hyrops fetalis (NIHF) consisted, 7% (1/15) of thoracic-lung disease, 7% (1/15) of chromosomal abnormality. In 86% of the cases no definitive etiological factor was determined. Outcomes of 15 NIHF pregnancies were termination of pregnancy in 4 cases, intrauterine and neonatal exitus in 1 and 9 case respectively and 1 healthy baby. The perinatal mortality rate of the present study group was 67%. CONCLUSIONS: Non-immune hydrops of newborn infant is associated with a high mortality rate and requires complex diagnostic and therapeutic procedures. Detailed ultrasound examination, fetal karyotyping, investigations for fetal infections and genetic diseases should be performed for all NIHF cases with a multidisciplinary approach.